Understanding the Board's Involvement in Information Technology Governance. Issue 2 (3rd April 2023) - Matta, Moksh; Cavusoglu, Hasan; Benbasat, Izak
ABSTRACT: The body of research examining the board's involvement in information technology governance (ITG) is expanding. While there is a growing consensus on the importance of this phenomena, the focal concept is still shrouded in confusion. Drawing upon theories on corporate governance, we develop a unifying analytical (Type 1) theory delineating the board's involvement in ITG. The proposed theory can be used by researchers for investigating this phenomenon, and by practitioners for training and policy formulation.